(untitled) (Boletín Micológico, 1997)
A taxonomic study has been carried out on 123 strains of the Vibrionaceae family isolated from bivalves and fishes in Valparaíso coasts. All strains were characterized with 86 phenotypic tests and clustering using SSM coefficient and the UPGMA linking analysis. The strains were clustered into three phena at 80% similarity level. These strains were identified as Aeromonas hydrophila, Vibrio sp. and Plesiomonas shigelloides .